1975
DOI: 10.1073/pnas.72.4.1446
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of an endoperoxide in human platelets: hemostatic defect due to platelet cyclo-oxygenase deficiency.

Abstract: The endoperoxide prostaglandin G2 (PGG2) induced platelet aggregation as well as the platelet release reaction (release of ADP and serotonin) when added to human platelet-rich plasma. Formation of a metabolite of PGG2 [8-(1-hydroxy-3-oxopropyl)-9,12L-dihydroxy-5,10-heptadecadienoic acid] and a lipoxygenase product [12L-hydroxy-5,8,10,14-eicosatetraenoic acid] accompanied the release reaction caused by aggregating agents such as collagen, ADP, epinephrine, and thrombin. Indomethacin inhibited the release react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(80 citation statements)
references
References 19 publications
(24 reference statements)
3
77
0
Order By: Relevance
“…These reactions induced by collagen are inhibited by indomethacin or aspirin which are known to inhibit collagen-induced generation of PGG2, PGH2 and TXA2 [2,3]. These arachidonic acid metabolites have been shown to induce secretion and aggregation [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reactions induced by collagen are inhibited by indomethacin or aspirin which are known to inhibit collagen-induced generation of PGG2, PGH2 and TXA2 [2,3]. These arachidonic acid metabolites have been shown to induce secretion and aggregation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These reactions induced by collagen are inhibited by indomethacin or aspirin which are known to inhibit collagen-induced generation of PGG2, PGH2 and TXA2 [2,3]. These arachidonic acid metabolites have been shown to induce secretion and aggregation [2,3]. Based on these observations, it has been suggested that PGH2 and TXA2 may play a role of crucial importance in the action of collagen [2- [4] have shown that PGH2 and its stable analogue U46619 induce phosphoinositide turnover to a small extent but counteract the inhibition by aspirin of collagen-induced phosphoinositide turnover.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of prostaglandin G2 to induce aggregation was inhibited by furosemide which is a competitive inhibitor of ADPinduced primary aggregation [ 3 61. A physiological role for prostaglandin Gz as a common mediator for various releasing agents has been demonstrated, and a case with functional lack of the platelet cyclooxygenase has been studied [16,17].It has been proposed by Salzman that prostaglandin synthesis is a prerequisite for the decrease of CAMP in human platelets [18]. Miller and Gorman have reported that prostaglandin G2 antagonized the increase of CAMP in response to prostaglandin El [19].…”
mentioning
confidence: 99%
“…The ability of prostaglandin G2 to induce aggregation was inhibited by furosemide which is a competitive inhibitor of ADPinduced primary aggregation [ 3 61. A physiological role for prostaglandin Gz as a common mediator for various releasing agents has been demonstrated, and a case with functional lack of the platelet cyclooxygenase has been studied [16,17].…”
mentioning
confidence: 99%
“…The endoperoxide prostaglandin G 2 (PGG2) derived from arachidonic acid is very potent in inducing platelet aggregatio n (Malmsten et al 1975). Mickel and Horbar (1974) reported that the platelet aggregation resulting from exposure to peroxidized arachidonic acid was abolished by prior treatment of the lipid peroxide with tocopherol and butylated hydroxytoluene .…”
Section: Methodsmentioning
confidence: 99%